Analisis Kesalahan Siswa dalam Menyelesaikan Soal Cerita Matematika Berdasarkan Prosedur Newman - M. Adzan Akbar; Laila Hayati; Eka Kurniawan; Nurul Hikmah (Pendidikan Matematika FKIP Universitas Mataram, 2022)
This study aims to find out the errors of the students of MTsN 2 Bima city in solving arithmetic story problems based on Newman's procedures for the 2021/2022 school year. The method used in this research is descriptive qualitative with written test and interview design. The population of this study were all eighth grade students of MTsN 2 Bima City for the Academic Year 2021/2022 which were distributed in eight classes. The sample class was selected for Class VII eight by giving written tests and interviews so that the criteria for students who obtained high, medium and low scores were obtained to analyze what students' mistakes were in solving the questions. As for the data collection techniques, namely observation and interviews. The analysis used is qualitative data where efforts are made by working with data, organizing data, sorting it into manageable units, synthesizing it, looking for and finding patterns, finding out what is important and what is learned, and deciding what can be done. told to others. Based on the results of data analysis, it was found that students' errors in solving math story problems based on the Newman Procedure with the criteria of high-ability students, namely the highest percentage of errors were found in the error stage in writing the final answer with an error rate of 33% and the lowest error rate was at the stage of reading the problem, transformation and process skills with an error rate of 0%, then for moderately capable students, the highest percentage of errors is at the stage of understanding the problem with an error rate of 58% and for the lowest error rate there is at the stage of reading problems, transformation problems and process skills with an error rate of 0%, Finally, for low-ability students, the highest percentage of errors is at the stage of understanding the problem, while the lowest error is at the stage of reading the problem with an error rate of 0%. This shows that we can see the results of the analysis of student errors in solving math story problems on social arithmetic material based on the Newman Procedure Class VII MTsN 2 Bima City.